You need to get rid of anything that is NOT "x", on the left side of the equation (i.e., of the equal sign). In this case, you achieve this by dividing both sides of the equation by 5.
-5x+50 = 25 -5x = 25-50 -5x = -25 x = 5
x = 25 / 3squared + 5
-5x2 = -75 x2 = 25 x = ±sqrt( 25 ) x = ±___
5x - 7=18 you add the seven to 18 and get 25 then you divide 25 by 5 to get x by itself and you will get 5 x=5
5x+3=25 5x = 22 (subtract 3 from each side) x = 22/5 (divide both sides by 5)
-5x+50 = 25 -5x = 25-50 -5x = -25 x = 5
30
5x = 25Divide both sides by 5:x = 5
5x - 1 = 24 5x - 1 + 1 = 24 + 1 5x = 25 5x/5 = 25/5 x = 5
x = 25 / 3squared + 5
-5x2 = -75 x2 = 25 x = ±sqrt( 25 ) x = ±___
5x - 11 - 36 is a math equation. 5x - 11 -36 can be simplified to read 5x- 47. I suspect that there is an equals missing, ie the question was/should be: "Solve for x in 5x - 11 equals -36" 5x - 11 = -36 → 5x = -25 → x = -5
5x - 7=18 you add the seven to 18 and get 25 then you divide 25 by 5 to get x by itself and you will get 5 x=5
It is a linear equation in the variable x. You can solve for x using algebra: -5x + 3 = -22 -5x = -25 -x = -5 x = 5
How to solve: 5x+2=27 5x=25 (Subtract 2 from each side) x=25/5=5 (Divide each side by 5) So, x=5
5x+3=25 5x = 22 (subtract 3 from each side) x = 22/5 (divide both sides by 5)
5x+25=10 5x+25-25=10-25 5x=-15 5x/5=-15/5 x=-3